Muscle Responses to Passive Joint Movements in Infants During the First Year of Life - Solopova, Irina A.; Zhvansky, Dmitry S.; Dolinskaya, Irina Y.; Keshishian, Elena S.; Selionov, Victor A.; Sylos-Labini, Francesca; Lacquaniti, Francesco; Ivanenko, Yury (Frontiers in Physiology, 2019)
Muscle tone represents one of the important concepts for characterizing changes in the state of the developing nervous system. It can be manifested in the level of activity of flexors and extensors and in muscle reactions to its passive stretching (StR) or shortening (ShR). Here we investigated such reactions in a cohort of healthy infants aged from 2 weeks to 12 months. We examined the presence and the characteristics of StR and ShR during slow passive cyclic flexion/extension movements (T3 s) in the hip, knee, ankle and elbow joints while awake infants were in the supine position. The results showed that most infants demonstrated prominent ShRs in response to passive joint rotations, although the StR was observed more frequently, suggesting that the ShR is an important component of adaptive motor behavior already at an early developmental stage. Interestingly, the occurrence of both StR and ShR in most muscles significantly decreased throughout the first year of life. Passive cyclic flexion/extension movements could also evoke rhythmic muscle responses in other joints or in the contralateral limb, however, such responses were predominantly observed in younger infants (<6 months). A noticeable manifestation of muscle reactions at an early developmental stage, along with spontaneous motor activity in this period of life, may reflect a formation of appropriate muscle tone and the processes underlying the self-organization of neural circuits. A substantial reduction of ipsilateral and contralateral muscle responses to passive movements with age is consistent with the idea of a functional reorganization of the motor circuitry during early development.